Marx y el reconocimiento (2006)
How far is Marxism from the paradigm of recognition? This article holds that, in spite of the main thesis of economic Marxism, there are in Marx many insights of an anthropology to which other person´s recognition is necessary for our individualization. By going back to Marx´s early works, the article explores his ideas about the due relations between genders, the place of the other in the human realization through work, and other dimensions in which the recognition plays a central role